2021
DOI: 10.1007/s41062-021-00590-1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of compressive strength of roller compacted concrete using regression analysis and artificial neural networks

Abstract: The compressive strength is most reliable parameter to evaluate the ability of concrete in resisting compression. The paper presents a study on prediction of the compressive strength of roller compacted concrete using multiple regression analysis (MRA) and artificial neural networks (ANN). The compressive strength of roller compacted concrete was obtained experimentally at 3, 7 and 28 days of curing. The samples were prepared by varying the percentage of cement and superplasticizer. The data were organized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In Figure 3 (also see Table 1), the compressive strength at 28 days curing and the environmental impact index (P) behaviour of FA admixed concrete corresponding to fly ash and binder ratio (FA/B; B = C+FA), fine aggregate and binder ratio (FAg/B) and coarse aggregate and binder ratio (CAg/B) is presented (see Figures 3-a to 3-f, respectively). It can be observed that the concrete mixes with high amount of cement produce high strength but with a compromised environment with high environmental impact (P) compared with the mixes with high FA and reduced cement, which produce low concrete strength (Fc28) but a more eco-friendly and eco-efficient environment with low impact (P) from the production and utilization of the concrete, which agrees with the studies [28][29][30][31][32][41][42][43][44][45][46][47][48][49][50][51][52][53], which studied the sorbent effect of increased FA in concrete. By implication, this shows that high FA/B ratio produce low strength compared to low FA/B as presented in Figures 3-a and 3-b.…”
Section: General Remarks On Collected Concrete MIX Data and The Envir...supporting
confidence: 87%
See 1 more Smart Citation
“…In Figure 3 (also see Table 1), the compressive strength at 28 days curing and the environmental impact index (P) behaviour of FA admixed concrete corresponding to fly ash and binder ratio (FA/B; B = C+FA), fine aggregate and binder ratio (FAg/B) and coarse aggregate and binder ratio (CAg/B) is presented (see Figures 3-a to 3-f, respectively). It can be observed that the concrete mixes with high amount of cement produce high strength but with a compromised environment with high environmental impact (P) compared with the mixes with high FA and reduced cement, which produce low concrete strength (Fc28) but a more eco-friendly and eco-efficient environment with low impact (P) from the production and utilization of the concrete, which agrees with the studies [28][29][30][31][32][41][42][43][44][45][46][47][48][49][50][51][52][53], which studied the sorbent effect of increased FA in concrete. By implication, this shows that high FA/B ratio produce low strength compared to low FA/B as presented in Figures 3-a and 3-b.…”
Section: General Remarks On Collected Concrete MIX Data and The Envir...supporting
confidence: 87%
“…An extensive literature search (experimental data, data arrangement, and tabulation), which has been conducted in this research work to collect the amount of concrete mix materials corresponding to the compressive strength at 28 days (Fc28) and the environmental impact, which has been evaluated by the method of life cycle assessment (LCA), has revealed the influence of fly ash (FA) proportion by partial or total replacement in the production of a more sustainable and eco-friendly concrete. During this first phase of the present research work, previous relevant research papers were reviewed [41][42][43][44][45][46][47][48][49][50][51][52] and data points relevant to this modeling and optimization exercise were collected and tabulated. Figure 1 shows the theoretical framework of the activities of this research work.…”
Section: Experimental Data Collectionmentioning
confidence: 99%